ANALYSIS OF THE USE OF MOBILE BANKING ON BCA SYARIAH CUSTOMER SATISFACTION - Haryawan, Marsvitodian Setya (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2024)
With the potential of a high Muslim population in Indonesia, it becomes an opportunity and challenge to develop the Islamic banking industry. The development of Islamic banking can be done by utiliusing technological developments. BCA Syariah is making optimal efforts to take advantage of the momentum of economic growth by accelerating digitalisation. Satisfaction can be influenced by several variables such as e-service quality, e-trust, Perceived Price, and Perceived Risk. This study uses a quantitative analysis approach with multiple linear regression analysis methods. The sampling technique in this study was purposive sampling by taking a sample of 100 respondents / customers who used BCA Syariah mobile banking. The research instrument used a questionnaire through the google form platform and was analysis using IBM SPSS Statistics 26. The results showed that E-Service Quality, and E-Trust had a significant positive effect while Perceived Price and Perceived Risk had a significant negative effect on BCA Syariah mobile customer Satisfaction. The coefficient of determination shows that 42.7% of the dependent variable can be explained by the independent variable and the remaining 57.3% is explained by other variables outside this study.